2020
DOI: 10.1002/cam4.2829
|View full text |Cite
|
Sign up to set email alerts
|

OSdlbcl: An online consensus survival analysis web server based on gene expression profiles of diffuse large B‐cell lymphoma

Abstract: Diffuse large B‐cell lymphoma (DLBCL) is the most common subtype of non‐Hodgkin lymphoma (NHL) and is a clinical, pathological, and molecular heterogeneous disease with highly variable clinical outcomes. Currently, valid prognostic biomarkers in DLBCL are still lacking. To optimize targeted therapy and improve the prognosis of DLBCL, the performance of proposed biomarkers needs to be evaluated in multiple cohorts, and new biomarkers need to be investigated in large datasets. Here, we developed a consensus Onli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…The impact of CD70 expression on DLBCL survival was further explored in the gene expression omnibus (GEO) and TCGA databases. High CD70 mRNA expression was also associated with shorter OS in a rituximab‐containing regimen‐treated DLBCL cohort (GSE117556) 38 and TCGA DLBCL cohort (dbGaP Study Accession: phs000178 39 ; figure generated by online OSDLBCL tool 40 ) (Figure 6F,G ).…”
Section: Resultsmentioning
confidence: 98%
“…The impact of CD70 expression on DLBCL survival was further explored in the gene expression omnibus (GEO) and TCGA databases. High CD70 mRNA expression was also associated with shorter OS in a rituximab‐containing regimen‐treated DLBCL cohort (GSE117556) 38 and TCGA DLBCL cohort (dbGaP Study Accession: phs000178 39 ; figure generated by online OSDLBCL tool 40 ) (Figure 6F,G ).…”
Section: Resultsmentioning
confidence: 98%
“…Patient samples with low, medium, or high expression of cyclin D3 have high, medium, or low expression of Fbxl8, respectively, underscoring Fbxl8 negatively regulates cyclin D3 expression in human lymphomas in a dose dependent manner. We further used a recently developed online tool to assess the lymphoma patients’ overall survival with gene expression [ 23 ], and observed that the low expression of Fbxl8 mRNA significantly correlated with reduced overall survival for lymphoma patients while the expression of cyclin D3 mRNA does not (Fig. 7c ).…”
Section: Resultsmentioning
confidence: 99%
“… 29 Kaplan–Meier analysis wsas derived from the TCGA database for DLBCL and generated by the OSdlbcl webserver. 30 Kaplan–Meier analysis for UCEC was derived from the TCGA database and generated by the UALCAN web platform. 31 Alterations of Cyclin D3 in UCEC data were derived from TCGA database and generated by the cBio Cancer Genomics Portal platform.…”
Section: Methodsmentioning
confidence: 99%